2014
DOI: 10.1515/hsz-2013-0262
|View full text |Cite
|
Sign up to set email alerts
|

N-homocysteinylation of apolipoprotein A-I impairs the protein’s antioxidant ability but not its cholesterol efflux capacity

Abstract: A high homocysteine (Hcy) level is a risk factor for atherosclerosis. Hcy can be added to proteins through a process known as N-homocysteinylation. This is thought to be a potential cause of atherosclerosis induction. We previously reported that N-homocysteinylated apolipoprotein A-I (N-Hcy-apoA-I) was identified in normal human plasma. In this study, the effect of N-homocysteinylation on the functions of apoA-I was examined. A kinetic study using dimyristoyl phosphatidylcholine (DMPC) liposomes indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Only a few studies have been reported about the relationship between Hcy and cholesterol efflux capacity [32, 33]. We previously reported that the cholesterol efflux capacity of apoA-I was not significantly reduced with N -homocysteinylation [15]. In the previous study the period of PMA stimulation was 3 days, indicating that the cells might be in the state of excessive differentiation to consider the possible effect of N -homocysteinylation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Only a few studies have been reported about the relationship between Hcy and cholesterol efflux capacity [32, 33]. We previously reported that the cholesterol efflux capacity of apoA-I was not significantly reduced with N -homocysteinylation [15]. In the previous study the period of PMA stimulation was 3 days, indicating that the cells might be in the state of excessive differentiation to consider the possible effect of N -homocysteinylation.…”
Section: Discussionmentioning
confidence: 98%
“…Using these different states of cells, we examined the effect of N -homocysteinylation on cholesterol efflux capacity of apoA-I. N -Hcy apoA-I was detected as a more positively charged band than intact apoA-I (Figure 6) and was defined as a percentage to total apoA-I, as described previously [15]. The variation in cholesterol efflux capacities of both apoA-I and N -Hcy apoA-I using THP-1 cells treated with PMA in different time intervals indicates similar trends, as compared to the values that reached the peaks at day 2 and then gradually decreased (Figure 7(a)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the measured proteoforms of ApoA-I resulting from single modifications will likely prove to have pathobiological and diagnostic significance as further clinical studies are performed. Apart from the mentioned ApoA-I proteoforms we also have searched for possible singly or multiply modified proteoforms of ApoA-I unequivocally resulting from nitration, chlorination and N-homocysteinylation, described to occur in a number of amino acid residues of ApoA-I [27,28]. These modifications of ApoA-I have been described to negatively affect the potency of ApoA-I in supporting the RCT pathway or its anti-inflammatory action and could serve as future clinically useful markers in classifying the percentage of crippled ApoA-I occurring in a specific sample.…”
Section: Discussionmentioning
confidence: 99%